Co0.85Se@carbon nanotubes surface-seeding grown on carbon microplates as superior anode material for sodium ion batteries. (10th May 2022) - Huang, Yanan; Wang, Minji; Huang, Mouzhi; Xiong, Yaping; Yang, Xiao; Miao, Zhengrui; Yang, Zhenyu; Yu, Ji
Highlights: The Co0.85 Se@CNT-CP composites were elaborately fabricated by a simple pyrolysis-selenization strategy. The fluffy 3D structure not only provides efficient pathways for quick electrons and Na + entrance, but also helps to reduce the volume-change effect during the charge@discharge cycles. Furthermore, the composites displayed a superior Na + storage performance. In-depth electrochemical kinetic investigations revealed the pseudocapacitive behavior of the composites for storge of Na + . Abstract: Transition metal selenides(TMSs) have been proposed as desirable anodes for sodium ion batteries(SIBs), whereas SIBs' cycling performance and rate capability limited their use. The Co0.85 Se@carbon nanotubes grown on the surface of carbon microplates(Co0.85 Se@CNT-CP) is derived from the metal organic frameworks(MOFs) by a simple pyrolysis-selenization strategy in this work. Co0.85 Se nanoparticles with different diameters are encapsulated in the top of carbon nanotubes or disperse on the surface of the carbon microplates. Such fluffy 3D hierarchical structure makes more sense in efficient pathways for fast electrons and Na + entrance, reducing the volume-change effect during cycle while also enhancing surface capacitive contributions. As expected, Co0.85 Se@CNT-CP composites exhibit superior rate performance: 222.5 mA h g −1 at a high rate of 5 A g −1 and excellent cycling performance: 306.4 mA h g −1 at a current density of 2 A g −1 over 800 cycles with high-capacity retention of 98%, when serving as an anode material for SIBs. Graphical abstract: Image, graphical abstract